2020
DOI: 10.36740/wlek202003125
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Education in Improving the Health Status of Students of Special Medical Groups

Abstract: The aim is to carry out the analysis of the disease incidence of students and to scientifically substantiate the directions of improving health and fitness activity in the physical education of the students of special medical groups. Materials and methods: The study was conducted at Zhytomyr National Agroecological University in 1992-2019. The main pedagogical experiment involved 681 students (209 males and 472 females, aged 17-22). The research methods included theoretical methods (the analysis and synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…Our results are confirmed by the conclusions of many scientists [1,4,12] who believe that the traditional form of physical education classes leads to a decrease in students' interest in physical education. Many scientists [7,16,20] argue that one of the most relevant forms of physical education organization is a sports-oriented form of training. Each student can choose the sport that is the most suitable and that brings pleasure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are confirmed by the conclusions of many scientists [1,4,12] who believe that the traditional form of physical education classes leads to a decrease in students' interest in physical education. Many scientists [7,16,20] argue that one of the most relevant forms of physical education organization is a sports-oriented form of training. Each student can choose the sport that is the most suitable and that brings pleasure.…”
Section: Discussionmentioning
confidence: 99%
“…The works of other scientists [13,14] mention that the number of students with low and below the middle level of somatic health increased from 60 % in 2009 to 85 % in 2019. The scientists [15,16] point out that some factors of life and socially hygienic living conditions, as well as studying at HEI do not provide optimal health for students. As a result of students testing, scientists [17] defined the initial level of physical fitness of the first-year students, among whom 18 % showed a low level; 49 % -lower than the middle (unsatisfactory grade); 20 % -the middle level (satisfactory grade); 13 % -above the middle (good grade).…”
Section: Introductionmentioning
confidence: 99%
“…It is the conditions and lifestyle with the use of various elements that relate to all aspects of health -physical, mental and spiritual -which can be considered the key to improving health and efficiency [15,16]. Physical exercises are of great importance for health promotion and disease prevention [17,18,19]. Scientists argue that physical education should provide an excellent level of health, high productivity of law enforcement officers and a range of recreational and rehabilitation measures [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Current scientific evidence indicates that university students neither practice enough physical exercise, nor comply with the global recommendations on Physical Activity (PA) established by the World Health Organization. This phenomenon is not limited to specific countries, but affects college students from all continents (Irwin et al, 2004;Clemente, Nikolaidis, Martins, & Mendes, 2016;Griban et al, 2020;Lipert et al, 2020;Mandić et al, 2020). In Saudi Arabia, recent studies addressing this aspect have reported low levels of PA practice (El Bcheraoui et al, 2016;Almutairi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%